Vaginal ecosystem modeling of growth patterns of anaerobic bacteria in microaerophilic conditions. (June 2017) - Medina-Colorado, Audrie A.; Vincent, Kathleen L.; Miller, Aaron L.; Maxwell, Carrie A.; Dawson, Lauren N.; Olive, Trevelyn; Kozlova, Elena V.; Baum, Marc M.; Pyles, Richard B.
Abstract: The human vagina constitutes a complex ecosystem created through relationships established between host mucosa and bacterial communities. In this ecosystem, classically defined bacterial aerobes and anaerobes thrive as communities in the microaerophilic environment. Levels of CO2 and O2 present in the vaginal lumen are impacted by both the ecosystem's physiology and the behavior and health of the human host. Study of such complex relationships requires controlled and reproducible causational approaches that are not possible in the human host that, until recently, was the only place these bacterial communities thrived. To address this need we have utilized our ex vivo human vaginal mucosa culture system to support controlled, reproducible colonization by vaginal bacterial communities (VBC) collected from healthy, asymptomatic donors. Parallel vaginal epithelial cells (VEC)-VBC co-cultures were exposed to two different atmospheric conditions to study the impact of CO2 concentrations upon the anaerobic bacteria associated with dysbiosis and inflammation. Our data suggest that in the context of transplanted VBC, increased CO2 favored specific lactobacilli species defined as microaerophiles when grown as monocultures. In preliminary studies, the observed community changes also led to shifts in host VEC phenotypes with significant changes in the host transcriptome, including altered expression of select molecular transporter genes. These findings support the need for additional study of the environmental changes associated with behavior and health upon the symbiotic and adversarial relationships that are formed in microbial communities present in the human vaginal ecosystem. Highlights: Increased luminal CO2 in the vagina favors lactobacilli over anaerobic bacteria. Microbiome shifts result in differential transporter and immune gene expression. CO2 enhanced L. jensenii more substantially than the other tested lactobacilli.